"I'm more aware now": perspectives from people with mild cognitive impairment (MCI), supporters and counsellors about the MAXCOG cognitive rehabilitation intervention. (2nd June 2020) - Regan, Bridget; Wells, Yvonne; O'Halloran, Paul
Abstract: Objectives: Cognitive Rehabilitation interventions have the potential to improve quality of life for people with MCI. We recently developed, trialled, and evaluated the use of the MAXCOG (Maximising Cognition) intervention—a very brief (four-session) face-to-face program focussing on individualised goals to improve function in daily life. Although the program assisted people reach their practical goals, we could not demonstrate broader changes to quality of life, mood, or carer burden. The aim of this study was to explore qualitatively the experiences of clients, supporters, and counsellors who participated. Method: Fifteen clients, fourteen supporters, and three counsellors were interviewed using the Most Significant Change technique. Subsequently, thirty-five narrative accounts were transcribed and subjected to thematic analysis following Braun and Clarke's (2006 ) model. Results: Key themes identified changes at two levels: specific changes (Putting strategies in place; and Doing it differently) and meta changes (More aware now; Facing up to life; and on top of anxiety and stress). Participants also mentioned supports and hindrances. Conclusion: The analysis provided a new perspective on the experiences of participants, supporters, and counsellors with the MAXCOG intervention, including identification of psychological changes that were not apparent from the quantitative analyses.